2019
DOI: 10.1159/000499510
|View full text |Cite
|
Sign up to set email alerts
|

oXiris® Use in Septic Shock: Experience of Two French Centres

Abstract: Background: Sepsis is a dysregulated host response to an infection and can result in organ dysfunctions and death. Extracorporeal blood purification techniques aim to improve the prognosis of these patients by modulating the unbalanced immune response. This study reports our experience with the use of the oXiris® membrane for septic shock patients requiring continuous renal replacement therapy (CRRT). Summary: Thirty-one patients were diagnosed with septic shock and underwent CRRT with the oXiris® membrane bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 20 publications
6
60
1
4
Order By: Relevance
“…Emerging evidence indicates the potential benefits of managing cytokine storm, via using steroid or IL-6/ IL-6-receptor blocking antibodies [3,6]. The capability of blood purification therapy in removing pathogenic antibodies or cytokines has been proven in multiple scenarios, but not in COVID-19 patients [7,8].…”
Section: Dear Editormentioning
confidence: 99%
“…Emerging evidence indicates the potential benefits of managing cytokine storm, via using steroid or IL-6/ IL-6-receptor blocking antibodies [3,6]. The capability of blood purification therapy in removing pathogenic antibodies or cytokines has been proven in multiple scenarios, but not in COVID-19 patients [7,8].…”
Section: Dear Editormentioning
confidence: 99%
“…Oxiris is a high permeability polyacrylonitrile (AN69) based membrane on which a surface treatment of a positively charged polyethylene is added onto the hemofilter. Thanks to this positive charge on the surface of the Oxiris filter -in addition to the bulk cytokine elimination in the mass of the membrane -endotoxin (negatively charged) adsorption takes place (13). In in-vitro studies, Oxiris filter emerges as a hemoperfusion device capable of eliminating both endotoxin and cytokine (29).…”
Section: Discussionmentioning
confidence: 99%
“…A relative decrease of 88% was observed in NIR. Lactatemia and pH improved significantly over time (13). In their study on 60 septic patients published in 2019, Turani et al found that CVVHDF with Oxiris filter improved basic cardiorenal and respiratory parameters and decreased NIR (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there was an 88% relative decrease in norepinephrine infusion (with stabilization of hemodynamic status) and a significant improvement in lactatemia and pH over time. These improvements were most evident in patients with intraabdominal sepsis and those with Gram-negative bacilli infection [95]. In a larger recent study, the medical records of 60 septic patients treated with CRRT using the oXiris set from April 2011 to December 2018 were reviewed-85% of patients had AKI.…”
Section: Prescription In Sepsismentioning
confidence: 99%